Relationship Between Maternal Fear and Anxiety About COVID-19 and Maternal Role Attainment in Mothers of Preterm Neonates - Mona Alinejad-Naeini; Parvaneh Zamani; Farshad Heidari-Beni (Iran University of Medical Sciences, 2023)
Background: Mothers of preterm neonates are more concerned about their babies' health than other mothers, which causes them to be worried and anxious. Meanwhile, the possibility of catching COVID-19 may increase their worries and anxiety and negatively affect their parenting roles. This study aims to determine the relationship between maternal fear and anxiety about COVID-19 and maternal role attainment in Iranian mothers with preterm neonates admitted to neonatal intensive care units (NICUs). Methods: This descriptive correlational study was conducted from June to July 2021 in 3 level-III NICUs in Tehran, Iran. The study samples were 211 mothers of preterm neonates who were recruited by convenience sampling. The study data were collected using a sociodemographic questionnaire, the Coronavirus anxiety scale, the fear of COVID-19 scale, and the maternal role adaptation scale in NICUs. The obtained data were analyzed utilizing the independent samples t-test, one-way ANOVA, and the Pearson correlation coefficient in SPSS software, version 23. P<0.05 was considered significant. Results: The mean scores of anxiety, fear, and maternal role attainment were 11.44±3.19, 26.49±5.92, and 57.61±11.95, respectively. There were weak, positive, and significant  relationships between anxiety and fear (r=0.385, P<0.001), anxiety and maternal role attainment (r=0.213, P=0.002), and some of x dimensions: Participation in care, distant mothering, interaction, and growth and development (P<0.05). There were also weak, positive, and significant relationships between fear and maternal role attainment (r=0.204, P=0.003) and some of x dimensions: Participation in care and growth and development (P<0.05).  Conclusion: Considering the relationship between the fear and anxiety of COVID-19 with maternal role attainment and the special importance of this issue in NICUs, evaluating the mental health of mothers with preterm neonates and implementing effective psychological interventions to support them is recommended.